Chemotherapy-induced ileal crypt apoptosis and the ileal microbiome shape immunosurveillance and prognosis of proximal colon cancer - Roberti, Maria Paula; Yonekura, Satoru; Duong, Connie P.M.; Picard, Marion; Ferrere, Gladys; Tidjani Alou, Maryam; Rauber, Conrad; Iebba, Valerio; Lehmann, Christian; Amon, Lukas; Dudziak, Diana; Derosa, Lisa; et al. (Nature Medicine, 2020)
The prognosis of colon cancer (CC) is dictated by tumor-infiltrating lymphocytes, including follicular helper T (TFH) cells and the efficacy of chemotherapy-induced immune responses. It remains unclear whether gut microbes contribute to the elicitation of TFH cell-driven responses. Here, we show that the ileal microbiota dictates tolerogenic versus immunogenic cell death of ileal intestinal epithelial cells (IECs) and the accumulation of TFH cells in patients with CC and mice. Suppression of IEC apoptosis led to compromised chemotherapy-induced immunosurveillance against CC in mice. Protective immune responses against CC were associated with residence of Bacteroides fragilis and Erysipelotrichaceae in the ileum. In the presence of these commensals, apoptotic ileal IECs elicited PD-1+ TFH cells in an interleukin-1R1- and interleukin-12-dependent manner. The ileal microbiome governed the efficacy of chemotherapy and PD-1 blockade in CC independently of microsatellite instability. These findings demonstrate that immunogenic ileal apoptosis contributes to the prognosis of chemotherapy-treated CC.
CRIS-Team Scopus Importer:2020-06-02